Ultra-Processed Food Consumption and Its Relationship with Diet Quality Among Malaysian Young Adults - Ali, Asma'; Ding, Natalie Xinyee; Zakaria, Noor Salihah; Kamarudin, Khairil Shazmin; Mohamed, Hamid Jan Jan; Zainuddin, Ahmad Ali; Yusof, Hayati Mohd (Malaysian Applied Biology, 2024)
The global rise in ultra-processed food (UPF) consumption presents potential public health challenges. UPFs, laden with additives and extensively marketed, are increasingly prevalent in modern diets. However, there is limited research on UPF consumption among Malaysian young adults, particularly its relationship with diet quality. This cross-sectional study aimed to investigate the relationship between UPF consumption and diet quality among 177 young adults aged 18 to 29 years from Terengganu, Johor, and Perak. A two-day 24-hour dietary recall was used to assess UPF intake, classified by the NOVA system, while diet quality was evaluated using the Standardised-Malaysian Healthy Eating Index (S-MHEI). The S-MHEI was adopted with the scores for each food group (adequacy component) calculated according to the recommended servings per food group expressed per 1,000 kcaL. Statistical analyses, including Spearman correlation, were conducted using SPSS version 25 to determine the relationship between UPF consumption and diet quality with statistical significance set at p<0.05. The median total energy intake was 1,417 kcaL (IQR=735.38), with UPFs contributing 38.6% of this intake. The median S-MHEI score was 44.65 (IQR=12.77), indicating that 74.6% of participants had poor diet quality. Statistical analysis found no significant relationship between UPF consumption and diet quality (p=0.395). Although no significant association was found, this study lays the groundwork for further research on nutrition and health among Malaysian young adults.